Correlation Between 123I-FP-CIT Brain SPECT and Parkinsonism in Dementia With Lewy Bodies: Caveat for Clinical Use. (January 2015) - Del Sole, Angelo; Perini, Giulia; Lecchi, Michela; Mariani, Claudio; Lucignani, Giovanni; Clerici, Francesca
Abstract : Introduction: Although parkinsonism is considered a core feature of dementia with Lewy bodies (DLB), it is occasionally mild or even absent. 123 I-FP-CIT SPECT has been accepted as a diagnostic support tool in this context, given that low striatal uptake is associated with neuronal loss. The aim of this retrospective study was to look for correlations between 123 I-FP-CIT uptake in the striatum and clinical extrapyramidal signs (EPSs) in patients with a diagnosis of probable DLB to clarify the extent to which the supporting role of 123 I-FP-CIT is related to motor impairment. Methods: Semiquantitative 123 I-FP-CIT uptake was analyzed and correlated with Unified Parkinson Disease Rating Scale Part III scores in a sample of 22 patients with a diagnosis of probable DLB and a wide range of EPSs. Results: A significant negative linear correlation between 123 I-FP-CIT uptake and Unified Parkinson Disease Rating Scale Part III score was found both in the caudate and the putamen ( r = −0.69 and −0.72, respectively, P < 0.001). Striatal uptake in patients with no or questionable EPS was comparable to that recorded in normal age-matched subjects (99% [22%] in the putamen) but significantly reduced in those with mild and severe EPS (43% [35%] and 30% [17%], respectively, P < 0.0001, but P = nonsignificant between mild and severe EPS). Conclusions: SPECT may be redundant when there are no doubts about the parkinsonism (ie, when it is absent or unequivocally present), but it may be helpful in identifying presynaptic nigrostriatal degeneration in patients with mild EPSs.